Jenis-Jenis Teknologi Komunikasi Sebagai Media Pembelajaran - Irma Handayani; Wahyudin Nur Nasution; Muhammad Irwan Padli Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Communication technology has become an integral part of education, especially as a learning media that supports the effective and efficient delivery of materials. This study aims to identify and analyze various types of communication technology used as learning media in formal educational settings. The research method employed is a literature review with a descriptive approach, examining reliable sources related to the development of communication technology and its application in learning. The results indicate that commonly used communication technologies as learning media include video conferencing software (such as Zoom and Google Meet), online learning platforms (such as Moodle and Edmodo), social media (such as WhatsApp and Telegram), and interactive multimedia technology. Each type of technology has its own advantages and disadvantages in supporting the learning process, depending on the context and needs of students and teachers. In conclusion, selecting appropriate communication technology can enhance learning effectiveness and facilitate interaction between teachers and students, making the learning process more engaging and meaningful.